Conceptual Framework and Designing for a Seafarers’ Health Observatory (SHO) Based on the Centro Internazionale Radio Medico (C.I.R.M.) Data Repository - Gopi Battineni; Getu Gamo Sagaro; Nalini Chintalapudi; Francesco Amenta (The Scientific World Journal)
Background. Health observatory (HO) models are helpful in gathering, analyzing, interpreting, and circulating reliable and quality information on population health and health service delivery. In this study, we proposed an HO conceptual model to enhance seafarer’s health, which subjects to disease trends. Methods. Three methods were followed during the study: a systematic collection of seafarer’s health data from the Centro Internazionale Radio Medico (C.I.R.M.) repository, an integrative review of existing seafarer’s policy, and both open and closed questionnaires were distributed to stakeholders to develop clinical knowledge. C.I.R.M. is the Italian Telemedical Maritime Assistance Service (TMAS). Results and Discussion. A three-layer HO framework was developed, and each layer had its components and functionalities. The proposed HO model integrated with the outcomes of the mentioned methods was working as the origin of the framework. In this way, we can design a standard infrastructure in ships and risk assessment conduction.